2021
DOI: 10.1186/s13027-021-00391-2
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Epstein-Barr virus infection and environmental xenobiotic exposure in cancer

Abstract: Epstein-Barr virus (EBV) is a herpesvirus associated with lymphoid and epithelial malignancies. Both B cells and epithelial cells are susceptible and permissive to EBV infection. However, considering that 90% of the human population is persistently EBV-infected, with a minority of them developing cancer, additional factors are necessary for tumor development. Xenobiotics such as tobacco smoke (TS) components, pollutants, pesticides, and food chemicals have been suggested as cofactors involved in EBV-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 207 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…This observation might reflect general life conditions, being more strenuous in East-Java and Sub-Sahara Africa, or relate to presence of subclinical Malaria, both potentially affecting EBV homeostasis [ 8 , 17 , 26 ]. Importantly, stress-induced corticoid hormones as well as DNA damaging agents/conditions are known to induce EBV lytic cycle and disturb EBV homeostasis [ 2 , 18 , 36 , 37 ]. Interestingly, the production/consumption of nitrosamine-containing salty fish recently increased in East-Java during prolonged periods of dry season [ 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might reflect general life conditions, being more strenuous in East-Java and Sub-Sahara Africa, or relate to presence of subclinical Malaria, both potentially affecting EBV homeostasis [ 8 , 17 , 26 ]. Importantly, stress-induced corticoid hormones as well as DNA damaging agents/conditions are known to induce EBV lytic cycle and disturb EBV homeostasis [ 2 , 18 , 36 , 37 ]. Interestingly, the production/consumption of nitrosamine-containing salty fish recently increased in East-Java during prolonged periods of dry season [ 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children in Indonesia are exposed to EBV at early age with high dose of EBV via saliva (pre-chewed food). Later in life chronic exposure to EBV carcinogens, such as formalin, tobacco additives, herbal drugs/oils, butyrate acid (dried meat) and nitrosamine (dried salty fish) are common, which can trigger aberrant and pathogenic EBV activity and malignancy [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we address the epidemiological and mechanistic evidence regarding a potential role of EBV in this malignancy. Taking into consideration that previous reported data suggested a cooperation between EBV and xenobiotics for carcinogenesis [26], here we propose potential mechanisms that involve an interplay between environmental factors such as tobacco smoke and EBV for developing lung cancer. However, additional experimental and epidemiological studies are warranted to confirm these possibilities.…”
Section: Introductionmentioning
confidence: 87%
“…Tobacco smoke also leads to viral lung infections with an increased incidence and severity due to airway epithelium oxidative damage [171]. Furthermore, tobacco smoking increases the oxidative stress that has the potential to promote the maintenance of viral genomes and EBV lytic reactivation [26]. EBV-positive BL cell lines studies have shown an increased ROS expression in both type I and III latency [172].…”
Section: Tobacco Smoke Impairs Immune Response Facilitating Ebv Infec...mentioning
confidence: 99%
“…Recently, Aguayo et al. addressed an interplay between the use of xenobiotics and EBV carcinogenesis 44 . Xenobiotics are found in tobacco, pollution, and food additives, and they can interrupt the EBV replicative cycle, resulting in cancer.…”
Section: Epidemiologymentioning
confidence: 99%